Modifikasi lingkungan dan manajemen pakan untuk mengatasi cekaman panas pada kambing perah di Gampong Lamlumpu Kecamatan Peukan Bada, Kabupaten Aceh Besar (Environmental modifications and feed management to cope heat stress of dairy goat in Lamlumpu Village, Peukan Bada Sub-District, Aceh Besar District) - Mariana, Elmy; Allaily, A; Latif, Herawati (Universitas Syiah Kuala, 2021)
The purpose of this service activity was the implementation of socialization and training on environmental modification and feed management to overcome heat stress in goat cattle at the dairy goat farm of the Lamlumpu Village Community, Peukan Bada Sub-District, Aceh Besar District. The method of implementing this activity are in the form of socialization, counseling, and training on a scheduled basis with material on dairy goat farming patterns in the tropics, modifying the environment to create a microclimate condition that is in accordance with the comfort zone for dairy cattle, and introduction of feed ingredients that have the potential to overcome heat stress. in the livestock. The results of this community service activity indicate that the implementation of environmental and feed modifications to overcome heat stress in goat cattle shows an increase in livestock production in the form of increased milk production, more comfortable environmental conditions, and a decrease in heat stress threshold in the livestock. In conclusion, environmental and feed modifications for dairy goats in Lamplumpu Village can improve microclimate conditions so that they are more comfortable and can cope with heat stress.